2013
DOI: 10.17221/252/2012-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Prunus interspecific progenies for resistance to Plum pox virus

Abstract: Salava J., Polák J., Oukropec I. (2013): Evaluation of the Prunus interspecific progenies for resistance to Plum pox virus. Czech J. Genet. Plant Breed., 49: 65-69.Sharka disease caused by the infection with the Plum pox virus (PPV) in stone fruit trees is worldwide the most devastating for stone fruit production. Until now, good sources of resistance to PPV within the peach group have not been available. There are no commercial cultivars of peach that are resistant to PPV. Other Prunus species are known to sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Former studies in Hungary have demonstrated that P. persicae 'Incrocio Pieri' , 'Mayfi re' and 'Michelini' have some PPV tolerance (Tóbiás et al, 1992). A fi ve-year-long experiment has been carried out by Salava et al (2013) in Poland with two rootstock-scion combina-tions ('Cadaman' x 'Cresthaven' and 'GF677' x 'Cresthaven') represented also in this study. In the present study new data were shown related to the PPV susceptibility of commonly used rootstock-scion combinations.…”
Section: Introductionmentioning
confidence: 99%
“…Former studies in Hungary have demonstrated that P. persicae 'Incrocio Pieri' , 'Mayfi re' and 'Michelini' have some PPV tolerance (Tóbiás et al, 1992). A fi ve-year-long experiment has been carried out by Salava et al (2013) in Poland with two rootstock-scion combina-tions ('Cadaman' x 'Cresthaven' and 'GF677' x 'Cresthaven') represented also in this study. In the present study new data were shown related to the PPV susceptibility of commonly used rootstock-scion combinations.…”
Section: Introductionmentioning
confidence: 99%